The correlation between serum bone metabolism indexes and bone disease and survival in newly diagnosed multiple myeloma patients - Linlin Huang; Yi Zhong; Qingxiao Chen; Donghua He; Gaofeng Zheng; Yang Yang; Xiaoyan Han; Wenjun Wu; Yi Zhao; Yi Li; Li Yang; Zhen Cai; et al. (Cancer Biology & Therapy)
Objective Myeloma-related bone disease (MBD) is one of the most common complications of multiple myeloma (MM). This study aims to investigate the correlation between serum bone metabolism indexes (BMIs), the clinical characteristics and prognosis of newly diagnosed MM (NDMM) patients. Methods: The serum BMIs of 148 patients with NDMM in a single hematological disease treatment center from April 2014 to December 2019 were analyzed retrospectively, including type I collagen amino terminal elongation peptide (PINP), β-C-terminal telopeptide of type I collagen (β-CTX) and N-terminal osteocalcin (N-MID). Other clinical indexes were simultaneously collected and the degree of bone damage in patients was evaluated. We explored the effect of serum BMIs on the prognosis and identified independent prognostic factors. Another 77 NDMM patients from April 2018 to February 2021 served as the validation cohort. Results: The area under the curve (AUC) predicted by β-C-terminal telopeptide of type I collagen (β-CTX), type I collagen amino terminal elongation peptide (PINP), and N-terminal osteocalcin (N-MID) for overall survival (OS) were 0.708, 0.613, and 0.538, respectively. Patients with high serum levels had shorter OS (p < .001, p = .004, p = .027, respectively). Cox multivariate analysis indicated that serum β- CTX、lactic dehydrogenase、hemoglobin and the degree of bone injury were independent prognostic factors. A COX regression model was established with a C-index of 0.782 and validated with a C-index of 0.711. Conclusion: The serum BMIs are correlated with the patients’ OS, and β- CTX can be an independent prognostic factor.